PENGARUH AGRESIVITAS PAJAK TERHADAP CORPORATE SOCIAL RESPONSIBILITY (CSR) : UNTUK MENGUJI TEORI LEGISTIMASI: Studi Empiris Pada Perusahaan Pertambangan Sub Sektor Batubara Yang Terdaftar Di Bursa Efek Indonesia - Kusumawati, Nugrahini; Afiah, Efi Tajuroh; Zahra, Surti; Komarudin, Mamay; Widodo, Wahyu; Azmi, Salsabila (Bussman Journal : Indonesian Journal of Business and Management, 2022)
In the Mineral and Coal Law no. 4 of 2009, mining is a mineral and coal exploitation activity which consists of stages of general investigation, exploration, feasibility studies, construction, mining, processing and refining, transportation and sales, and post-mining activities. Coal mining is the mining of carbon deposited rock found in the earth, including solid bitumen, peat, and asphalt rock. The purpose of this study was to determine the effect of tax aggressiveness on corporate social responsibility in coal mining sub-sector companies in 2017- 2021. The method used in this study is a quantitative method. The variables in this study consist of the dependent variable, namely corporate social responsibility, while the independent variables are tax aggressiveness and the control variables are capital intensity, company size, return on assets, and leverage. The population in this study is the coal sub-sector mining companies listed on the Indonesia Stock Exchange in 2017-2021, amounting to 22 companies. The number of samples that have complete financial statements are 10 companies with a research period of 5 years so that a sample of 50 samples is obtained with the sampling technique using the purposive sampling method. The results showed that the tax aggressiveness variable based on the results of the t-test obtained a Tcount of 0.770 <Ttable 1.67655. The conclusion of this study is that partially shows that tax aggressiveness has no effect on corporate social responsibility